Role of spliceosome proteins in the regulation of glucocorticoid receptor isoforms by cortisol and dehydroepiandrosterone. (June 2017) - Buoso, Erica; Galasso, Marilisa; Ronfani, Melania; Serafini, Melania Maria; Lanni, Cristina; Corsini, Emanuela; Racchi, Marco
Graphical abstract: Abstract: Dehydroepiandrosterone (DHEA) can counteract the activity of cortisol by modulating the glucocorticoid receptor β (GRβ) expression and antagonizing the binding of GRα to the glucocorticoid responsive element (GRE) in RACK1 ( R eceptor for A ctivated C K inase 1) promoter. These observations are important in the context of immunosenescence and can be extended to recognize a complex hormonal balance in the control of GR isoform expression and consequently in the expression of GR responsive genes. To elucidate the mechanism of DHEA on GR alternative splicing, we investigated its possible involvement in the expression of proteins such as the S erine/arginine (SR)- R ich S plicing F actors (SRSF) regulating GR splicing, specifically SRSF9 and SRSF3 also known as SRp30c and SRp20 respectively. We demonstrated that DHEA can induce the up-regulation of GR mRNA which is preferentially directed toward the β isoform. The effect is due to an increase in expression of the splicing factor SRSF9. On the other hand cortisol up-regulated SRSF3, the splicing factor promoting GRα isoform. We demonstrated that DHEA and cortisol modulate SRSF9 and SRSF3 in a different way and our data suggest that the anti-glucocorticoid effect of DHEA, among other mechanisms, is also exerted by modulating the expression of proteins involved in the splicing of the GR pre-mRNA.